Analysis of Pro-Environmental Behavior in College Students: A Literature Review - Nur Rohmah, Imawati; Salsabila, Zaahirotus; Andriyani, Andriyani; Wati, Intan Ratna (LifeSciFi, 2024)
The Sustainable Development Goals (SDGs) serve as a global framework designed to address pressing social, economic, and environmental challenges, aiming to promote sustainable development and equitable progress worldwide. Higher education plays a critical role in advancing the implementation of these sustainable development goals and exploring how strategies based on Value-Belief-Norm (VBN) theory can influence pro-environmental behaviors among students. This study also seeks to emphasize the importance of higher education in facilitating the transition of values and beliefs in younger generations toward more environmentally responsible behaviors. It aims to empower younger generations to better understand their role in environmental preservation. These strategies could provide an effective approach to empowering higher education in supporting sustainability. This study adopts a literature review method, referring to previous research and current phenomena to analyze the role of VBN theory in promoting sustainability within higher education. Findings indicate that the VBN theory can enhance sustainable behavior among students, leading to improved sustainability performance in higher education. Furthermore, this study contributes to the development of VBN theory by exploring the influence of personality traits on students’ sustainable behaviors. It also offers essential insights into how higher education institutions can develop more effective communication strategies and policies to foster a sustainable environment. These insights are expected to inform the design of strategies that not only enhance student behavior but also help higher education institutions achieve sustainability goals aligned with global SDG initiatives.